Parasitoid telur Lalatjala (Chrysopa sp.) pada ekosistem jambu mete di lombok - Bambang Supeno (Jurnal Entomologi Indonesia, 2007)
The objective of this research was to identify parasitoids associated with eggs of Chrysopa in Lombok cashew ecosytem. Parasitoids were surveyed by collecting eggs of Chrysopa from cashew plantations. Total of 5900 individual parasitoids from a single species were collected from eggs of Chrysopa with parasitization level was approximately 47.0%-85.50%. The parasitoid was identified as Telenomus cyrus (Hymenoptera: Scelionidae).